The MOR2 database: building integrated datasets for social-ecological analysis across cultures and disciplines - Laituri, Melinda J., author; Linn, Sophia, author; Fassnacht, Steven R., author; Venable, Niah, author; Jamiyansharav, Khishigbayar, author; Ulambayar, Tungalag, author; Allegretti, Arren Mendezona, author; Reid, Robin, author; Fernandez-Gimenez, Maria, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
This paper describes the construction of a complex database for social-ecological analysis in Mongolia. As a National Science Foundation (NSF)-funded Dynamics of Coupled Natural and Human (CNH) Systems, the Mongolian Rangelands and Resilience (MOR2) project focused on the vulnerability of Mongolian pastoral systems to climate change and adaptive capacity. To study this phenomenon, our team is made up of a group of hydrologists, social scientists, geographers, and ecologists collecting data across the Mongolian landscape over three years. This dataset is unique in that it captures multiple types of field data: ecological, hydrological and social science surveys; remotely-sensed data, participatory mapping, local documents, and scholarly literature. We describe the content, structure, and organization of the database and explain the development of data protocols and issues related to access and sharing. Descriptions of data analysis are included to demonstrate the utility of the database as well as its limitations. We conclude with a description of the challenges in creating a cross-cultural and multi-disciplinary database and lessons learned.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: database; interdisciplinary; Mongolia; social-ecological analysis